Objective prediction of pure tone thresholds in normal and hearing-impaired ears with distortion product otoacoustic emissions and artificial neural networks - Hugo, Rene (University of Pretoria, 2013)
Thesis (DPhil (Communication Pathology))--University of Pretoria, 2007.